A Analisis Keterampilan Teknik Shooting Cabang Olahraga Bola Tangan Dalam Final IHF Men’s world Championship 2023 – Denmark Vs France - Amanda Audya, Voney Kitty; Susanto, Indra Himawan; Wismanadi, Himawan; Wahyudi, Heri (Jurnal Speed (Sport, Physical Education, Empowerment), 2024)
At the 2023 International Handball Federation (IHF) Men's World Championship, Denmark successfully defended its title by beating France with a final score of 34-29. Both teams have extraordinary shooting skills. Therefore, the author wants to analyze the Strengths, Weaknesses, Opportunities, Threats of the shooting skills of both teams in the final match. The researcher's aim is to analyze shooting techniques to determine strengths, weaknesses, opportunities and threats, which can serve as a guide and reference for implementing shooting technique training. The research method uses SWOT analysis with the results of observing the success and failure of shooting technique skills carried out by Danish and French players. The results show that when doing a flying shot, it is when flying that has an efficient effect on getting success in getting points. On the other hand, Denmark has a weakness in Fall shots and France has a weakness in Jump shots because the percentage of failures is higher than successes. Failure of this type of shooting can be analyzed based on mechanical factors in shooting such as stride length and movement distance which must be increased. Keywords: SWOT Analysis, Shooting, Handball, IHF 2023